1995
DOI: 10.1007/bf00195719
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of germination of embryos isolated from dormant and nondormant barley grains by manipulation of endogenous abscisic acid

Abstract: Abstract. Dormant and non-dormant barley (Hordeum distichum L.) grains with identical genetic backgrounds were obtained by maturing grains under different climate conditions. When isolated embryos from dormant grains were incubated in a well containing a fixed volume of water (300 gl), the germination rate and percentage were dependent on the embryo number per well. A higher embryo number per well was correlated with a lower germination rate and percentage. However, this was not the case for the embryos isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
98
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 27 publications
13
98
1
2
Order By: Relevance
“…For example, Weidner et al (1993) demonstrated a relationship between phenolic acids and barley dormancy with an increase in total and free phenolic acid content coinciding with the pattern of dormancy after flowering and post ripening. In addition it was demonstrated that ferulic and sinapic acid retarded germination of ripening barley embryos, and Wang et al (1995) showed that an increased level of hydrogen peroxide reduced the inhibitory effect of ABA. The biochemistry of dormancy is complex and covered in a large and diverse literature.…”
Section: Dormancymentioning
confidence: 99%
“…For example, Weidner et al (1993) demonstrated a relationship between phenolic acids and barley dormancy with an increase in total and free phenolic acid content coinciding with the pattern of dormancy after flowering and post ripening. In addition it was demonstrated that ferulic and sinapic acid retarded germination of ripening barley embryos, and Wang et al (1995) showed that an increased level of hydrogen peroxide reduced the inhibitory effect of ABA. The biochemistry of dormancy is complex and covered in a large and diverse literature.…”
Section: Dormancymentioning
confidence: 99%
“…For starchy mono-cotyledons, the seeds of barley and wild oat were most frequently studied (for example Dyer 1993;Wang et al 1995;Han et al 1996). For the studies of the dormancy control in oily annuals, lettuce achenes (e.g., Fountain and Bewley 1973;Hsiao and Vidaver 1989) and sunflower seeds (e.g., Srivastava and Dey 1982;Gay et al 1991) were used, whereas apple seeds, in parallel to hazel (e.g., Jarvis et al 1968) and Acer (e.g., Pinfield and Dungey 1985), seem to be the most extensively investigated model material for studies of dormancy in oily perennial dicotyledonous seeds.…”
Section: Germination and Dormancy In Seedsmentioning
confidence: 99%
“…Instead, responsiveness of isolated embryos to exogenous ABA is highly correlated with dormancy expressed in the intact grains from several species, such as wheat (Walker-Simmons, 1987;Morris et al, 1989;Gerjets et al, 2010), barley (Wang et al, 1995;Benech-Arnold et al, 1999Leymarie et al, 2008;Barrero et al, 2009), oat (Corbineau et al, 1991, sorghum (Steinbach et al, 1995) and rice (Gianinetti and Vernieri, 2007). Different embryo sensitivity to ABA can result from differential signalling activity or efficiency of molecular components of the ABA signal transduction pathway, although differential catabolism rates might also affect embryo responsiveness to exogenous ABA (Benech-Arnold et al, 2006).…”
Section: Hormonal Regulation Of Dormancymentioning
confidence: 99%
“…The expression of dormancy in barley and oat grains is associated with maintenance of a higher ABA content, while embryo ABA decreases sharply in non-dormant grains or dormant ones placed in conditions that do not allow expression of dormancy (Ried and WalkerSimmons, 1990;Wang et al, 1995;Jacobsen et al, 2002;Benech-Arnold et al, 2006;Millar et al, 2006;Leymarie et al, 2008;Hoang et al, 2013b). However, ABA metabolism is also modulated by grain moisture content.…”
Section: Watermentioning
confidence: 99%